1074 Ventricular Index Remains Static Between 24 and 34 Weeks. (October 2012) - Gnanasakaran, R; Shim, R; Boyle, M; Tarrant, A; Ryan, S; McCallion, N
Abstract : Background: Intraventricular hemorrhage (IVH) and Post Hemorrhagic Ventricular Dilation (PVHD) are serious complications in premature infants and are associated with a high risk of disability. These conditions can be diagnosed by measuring the ratio of ventricular size to overall hemisphere width using Ventricular Index (VI), which was designed for use in infants >40 weeks gestation. Aim: To establish Normal Ranges and Median Values for VI. Method: The Ventricular sizes of cranial ultrasounds of infants with a Gestational age at Scan under 34 weeks were assessed using VI. Ultrasounds with Grade III or IV IVH or PVL were excluded from the study. Ventricular index was measured. Results: From 255 infants, 816 cranial ultrasounds were reviewed. The Normal ranges for LVI were 0–0.69 and RVI were 0.23–0.88. The Median Values for both LVI and RVI are 0.31 overall and there was no significant change with increasing gestational age. Conclusion: The Median Values for VI did not significantly change with Gestational Age at scan, and it is appropriate to use the same reference ranges for gestation across all gestation.